The Correlation between Sitting Duration and Physical Activity with the Quality of Life of the Elderly in Sidoarjo - Widanti, Herista Novia; Arti, Widi (FISIO MU: Physiotherapy Evidences, 2025)
Introduction: The rising elderly population in Indonesia brings significant challenges related to the decline in quality of life due to sedentary behavior, including prolonged sitting and low levels of physical activity. Understanding the impact of sitting duration and physical activity on the quality of life of older adults, especially in Sidoarjo, is crucial for developing effective interventions to improve their quality of life. This study aims to examine the relationship between sitting duration, physical activity, and quality of life among elderly individuals in Sidoarjo, Indonesia. Methods: This cross-sectional study employed a quantitative correlational approach. The sample size consisted of 60 elderly individuals aged 60-75 years who had active mobility. Data were collected using the World Health Organization Quality of Life (WHOQOL) questionnaire to assess quality of life and the International Physical Activity Questionnaire (IPAQ) to measure physical activity levels. Pearson correlation tests were used to analyze the data. Results: There was a significant negative correlation between sitting duration and quality of life in the psychology domain (r = -0.608; p = 0.001), social relationships (r = -0.595; p = 0.001), and environment (r = -0.474; p = 0.001). In contrast, physical activity had a significant positive correlation with quality of life in the physical domain (r = 0.401; p = 0.001), psychology (r = 0.505; p = 0.001), social relationships (r = 0.501; p = 0.001), and environment (r = 0.315; p = 0.014). Conclusion: Prolonged sitting duration has a negative impact on the quality of life of the elderly, especially in the psychology, social relationships, and environment aspects. In contrast, physical activity is positively related to increased quality of life in the physical, psychology, social relationships, and environment aspects.